Peran Karang Taruna “Tunas Harapan” Dalam Melestarikan Tradisi Tari “Singo Mengkok Dan Leang-Leong” Di Desa Drajat, Kecamatan Paciran, Kabupaten Lamongan - Moh. Syarif Hidayat (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
The preservation of traditional art has become an important challenge amid the wave of modernization that affects the mindset and interest of the younger generation toward local culture. This condition requires the involvement of various elements of society, including youth organizations, in maintaining the sustainability of cultural heritage. This study aims to analyze the role of the Karang Taruna “Tunas Harapan” of Drajat Village in preserving the Singo Mengkok and Leang-Leong dance traditions as part of the cultural identity of the Drajat Village community, Paciran District, Lamongan Regency. This study uses a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The results show that Karang Taruna “Tunas Harapan” acts as the main driver of art preservation through performer regeneration, routine rehearsals, involvement in village cultural activities, digital media promotion, and collaboration with the village government and community leaders. However, preservation still faces obstacles such as limited funding, low interest among some youths, and minimal historical documentation.